Performance and Religion: Dancing Bodies in Macedonian Orthodox Fresco Painting - Zdravkova Djeparoska Sonja (ARTS, MDPI, 2021)
Although dance as a topic has been explored through various theoretical and thematic discourse, little attention has been paid to the presence of dance motifs in Christian imagery. An examination of Orthodox Macedonian medieval fresco painting provides a fascinating point of entry into this overlooked subject. Analysis reveals the presence of two dominant approaches, conditioned primarily by the position of dancing in the philosophical-ethical discourse present in the Bible and other late antique and medieval theological texts. Some frescoes and icons show the body as a channel through which the Lord is glorified. Others show it as an instrument and reflection of immorality instigated by demonic powers. As in each approach, the bodies have differing semantic qualities, valuable information can be obtained about the performing practices present in this historical period
Keywords: dance; dance bodies; religion; frescos; religious icons; Middle Ages; Macedonia